2017
DOI: 10.1007/s12194-017-0411-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the radiation dose to the pyramidal tract using tractography in treatment planning for stereotactic radiosurgery

Abstract: In stereotactic radiosurgery for intracranial lesions, optimization of the dose to the at-risk organs is important to avoid neurological complications. We aimed to quantify the dose to the pyramidal tract (PT) and improve treatment planning for gamma knife radiosurgery by combining tractography. Pyramidal tractography images were depicted in 23 patients with lesions adjacent to the PT and fused with stereotactic magnetic resonance images. We regarded the PT as an at-risk organ and performed dose planning. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Additionally, studies have shown XRT side effects in both gray (Bahrami et al, 2017) and white matter, although it is still largely unclear how variable sensitivity to radiation injury is across various regions of the brain (Connor et al, 2017). Kawasaki et al (2017) show that tractography can help evaluate how radiation from XRT differentially affects WM regions and pathways. This knowledge, together with an understanding of how damage to such regions and pathways affects cognitive processes, could be used in the future to further optimize radiation treatment planning.…”
Section: The Acoustic Radiation: Functional and Clinical Implicationsmentioning
confidence: 98%
“…Additionally, studies have shown XRT side effects in both gray (Bahrami et al, 2017) and white matter, although it is still largely unclear how variable sensitivity to radiation injury is across various regions of the brain (Connor et al, 2017). Kawasaki et al (2017) show that tractography can help evaluate how radiation from XRT differentially affects WM regions and pathways. This knowledge, together with an understanding of how damage to such regions and pathways affects cognitive processes, could be used in the future to further optimize radiation treatment planning.…”
Section: The Acoustic Radiation: Functional and Clinical Implicationsmentioning
confidence: 98%
“…Hubo diferencias significativas en el índice de homogeneidad (ratio entre la dosis máxima y la isodosis de prescripción), siendo de 1,23 en promedio en la planificación sin tractografía, y de 1,33 en la planificación con tractografía (p = 0,009). Kawasaki (2017), estudió prospectivamente 23 pacientes con lesiones supratentoriales adyacentes al tracto piramidal, estudiados con tractografía y tratados con gamma knife. La dosis máxima al tracto piramidal se redujo de 11,9 a 10,5 Gy en los planes con tractografía integrada, versus los planes sin esta integración (p < 0,05).…”
Section: Métodounclassified
“…A study compared the predicted radiation does to the pyramidal tract with and without the use of including the tracts. The study found there was a significantly reduced dose to the pyramidal tract without dose reductions in the area of pathology [21]. The study used the cerebral peduncles, posterior limb of the internal capsule, and primary motor cortex selected on T1w MRI as the seed points for tractography.…”
Section: Virtual Dissection Of Eloquent Wm Tractsmentioning
confidence: 99%
“…This method has been evaluated in several studies of cohorts including brain metastasis along with other benign neurological conditions. The largest identified study contained 20 patients with brain metastasis (and three patients with other conditions), and they compared SRT plans with and without including the CST as an OAR, finding that this significantly reduced the maximum radiation dose to the CST but not the total dose to 95% of the tract [21]. However, this study did not use the tractography-guided treatment plan for administration of the dose to the patients.…”
Section: Applications In Brain Metastasesmentioning
confidence: 99%